The mediated world a new approach to mass communication and culture - Mindich, David T. Z. 1963- (Rowman & Littlefield, 2020)
"Written for students to engage in how we communicate with one another, how we understand our world, and how media shapes us. Using stories of our media and culture, this book offers historical context, integrates new media advances into each chapter, and takes an interdisciplinary approach to the study of communication"--